Perbandingan Kecerdasan Interpersonal dan Hasil Belajar Biologi Siswa Antara yang Dibelajarkan dengan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dan Jigsaw III - Asniati Samad; Muhammad Danial; Muhammad Wiharto (UNM Journal of Biological Education, 2018)
This research is quasi experiment, pretest-posttest nonequivalent control group design. The aims is to know about the difference of interpersonal intelligence and students’ biology learning achievement who taught by cooperative learning model tipe two stay two stray and jigsaw III for excretion subject matter XI science SMAN 4 Parepare. Research data about interpersonal intelligence got from questionnaire of interpersonal intelligence and data about Students’ Biology Learning Achievement got from value of learning achievement test. The result of research show that mean of students’ interpersonal intelligence who taught by cooperative learning model type Two Stay Two Stray is 83,54. The result of research show that mean of students’ interpersonal intelligence who taught by cooperative learning model type Jigsaw III is 83,79. The mean of students’ Biologi learning achievement who taught by cooperative learning model type Two Stay Two Stray is 83,54 is 78,67. The mean of students’ Biologi learning achievement who taught by cooperative learning model type Jigsaw III is 84,75. The result of test of between subjects effects from MANCOVA, so we got sig. value of learning achievement 0,000 and 0,736 for interpersonal intelligence. So, the conclusion is there are significant difference of students’ biology learning achievement who taught by cooperative learning model tipe two stay two stray and jigsaw III for excretion subject matter XI science SMAN 4 Parepare and not different in interpersonal intelligence.